Regulatory Frameworks and Governance in Islamic Banking: A Bibliometric Review of Compliance Standards - Loso Judijanto; Dadin Solihin; Pardin Lasaksi; Diah Fauziah; Rita Nurnaningsih (West Science Social and Humanities Studies, 2024)
Over the past few decades, the global discourse on environmental sustainability and climate change has catalyzed a profound transformation in economic paradigms, giving rise to the concept of the green economy. This paradigm emphasizes the integration of environmental considerations into economic activities to foster sustainable development and mitigate environmental degradation. In the context of Islamic banking, which operates under the principles of Sharia, there is a growing recognition of the importance of aligning financial practices with ethical and social values, including environmental stewardship. This bibliometric review explores the regulatory frameworks and governance structures in Islamic banking with a focus on compliance standards related to environmental sustainability. Through a systematic analysis of scholarly literature, this study aims to shed light on current trends, key areas of focus, and potential areas for improvement in ensuring environmental sustainability within Islamic banking operations.